Proses Fonologis pada Tuturan Bahasa Indonesia oleh Idol Penutur Korea dalam Variety Show â€œHalo82: NCT Dreamâ€ : Phonological Process of Indonesian Speech by Native Korean Idols on the Variety Show â€œHalo82: NCT Dreamâ€ - Ni Gusti Ayu Dhyana Widyadewi; Lia Maulia Indrayani (Kantor Bahasa Provinsi Maluku, 2022)
This study discusses the phonological process of Indonesian speech carried out by native speakers of the Korean idol NCT Dream in the variety show Halo82. The study's purpose is to find out the phonological processes that occur in the speech of Indonesian words carried out by Korean native speakers. This research uses the descriptive qualitative method to describe every phonological process that occurs in each speech produced. The data collection technique used was simak bebas libat cakap and catat with data in the form of 24 words sourced from the speech of Korean speakers in the Halo82 variety show video on YouTube. The data obtained were processed by data reduction techniques, data presentation, and drawing conclusions. Based on the analysis of words spoken by the idol NCT Dream in the variety show Halo82, there are 13 phonological processes in the form of 7 epenthesis, 8 final consonant deletions, 13 vowel deviation, 1 /l/deviations, 1Â /r/Â deviations, 1 metathesis, 4 taps â€˜râ€™ â€“ trill â€˜râ€™ deficiency, 8 strengthening, 1 prevocalic voicing, 1 affrication, 1 consonant devoicing, 1 nasalization, and 2 blackenings. Keywords: phonological process, speech, Indonesian and Korean, NCT, Halo82